Analisis pola tekanan kalimat: Video animasi fawaz wa naura episode al-suja’ah - Az-Zahrah, Alvia Farah; Hasaniyah, Nur (Maliki Interdisciplinary Journal, 2025)
The pattern of an-nabr or stress is a study of sound phonology which contains patterns of speech emphasis on letters in a word or on words in a sentence. In this study, researchers used the animated video of Fawaz and Naura with the title Al-Suja'ah in the first minute uploaded on Sukardi Hasanudin's youtube channel.The purpose of this research is to find out the nabr or pressure patterns used by the characters in their conversations. This research resulted in finding 12 pressure patterns, namely 7 pressure patterns with rules according to the speaker's will, 3 pressure patterns with command sentence rules and 2 pressure patterns with Adawatul Istifham rules. These findings indicate that the use of stress patterns in the animated video not only functions as an intonation marker, but also as a communication tool that clarifies the speaker's intentions and emotions.